(untitled) (Світ фінансів, 2017)
Мокрицька А. Б. Сучасні реалії, практика та проблеми бюджетного планування видатків на охорону здоров’я. Розглянуто та проаналізовано діючу практику бюджетного планування видатків на охорону здоров’я в Україні. Висвітлено проблеми формування та розподілу видатків місцевих бюджетів на одну з найважливіших сфер суспільних послуг – охорону здоров’я. Mokrytska A. Modern realities, practice and problems of the budgetary planning of charges on a health protection. Operating practice of the budgetary planning of charges on a health protection in Ukraine is considered and analysed. The problems of forming and allocation of charges of local budgets on one of major spheres of public services – health protection are reflected.